Targeting bromodomain and extra-terminal proteins to inhibit neuroblastoma tumorigenesis through regulating MYCN - Shi, Xiyao; Wang, Ying; Zhang, Longhui; Zhao, Wenjie; Dai, Xiangpeng; Yang, Yong-Guang; Zhang, Xiaoling (Frontiers in Cell and Developmental Biology, 2022)
Bromodomain and extra-terminal domain (BET) family proteins play important roles in regulating the expression of multiple proto-oncogenes by recognizing acetylation of histones and non-histone proteins including transcription factors, which subsequently promote tumor cell proliferation, survival, metastasis and immune escape. Therefore, BET family proteins are considered attractive therapeutic targets in various cancers. Currently, blocking of the BET proteins is a widely used therapeutic strategy for MYCN amplified high-risk neuroblastoma. Here, we summarized and reviewed the recent research progresses for the critical function of BET proteins, as an epigenetic reader, on tumorigenesis and the therapeutic potential of the BET/BRD4 inhibitors on MYCN amplified neuroblastoma. We also discussed the combined therapeutic strategies for BET inhibitor-resistant neuroblastoma.